How does $(iwl + \frac{1}{iwc})^2$ equal to $(wl - \frac{1}{wc})^2$?

Let me clarify. In physics there is the impedance which is a complex number
Z = R + iwl + 1/iwc

R, w, l, and c, are constants; i = $\sqrt-1$
According to my book: |z| = $\sqrt{R^2 + (wl - \frac{1}{wc})^2}$

The real part of Z (i.e. R) squared gives R^2; the imaginary part squared gives the second term under the root, but I don't get how they're equivalent.


They're not:

$$\left( iwl + {1 \over iwc} \right)^2 = \left( iwl - {i \over wc} \right)^2 = i^2 \left( wl - {1 \over wc} \right)^2 = - \left( wl - {1 \over wc} \right)^2$$

  • $\begingroup$ I clarified the question $\endgroup$ – user35687 Jan 20 '15 at 21:05
  • $\begingroup$ In which case yes, because for any complex number $z$ can be written as $z = a + bi$ for $a, b$ real, and has modulus $z = \sqrt{a^2 + b^2}$. Now apply that formula to your $Z$. $\endgroup$ – Simon S Jan 20 '15 at 21:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.